The Impact of New Retail Strategy and Strategy to Win The Business Case Study of Maicih - Ayu Mulatsasi, Dyah; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2016)
Abstract - The purpose of this research is to address the business impact and consumer’s opinion towards Maicih’s retailing distribution strategy. And also to propose integrated strategy that suit for Maicih’s current business situation. Consumer analysis by using Consumer Style Inventory (CSI) was conducted to find out the impact of Maicih’s retailing strategy towards company’s business and consumer’s opinion. After that, there are internal and external analysis to propose a potential strategy that suit for Maicih’s current business situation. Internal analysis consists of Maicih’s current STP, Marketing Mix and Value Chain analysis. While the external analysis consists of PEST and Porter’s Five Forces analysis. There also Diamond Strategy of Maicih. SWOT analysis conducted to identify Maicih’s condition further. The results of SWOT analysis translated into TOWS analysis to formulate alternative strategies to cover the root cause of Maicih’s business issue. Many alternative strategies that have appeared being analyzed by using CARVER model to prioritize the important strategy. The chosen strategies are leading to potential strategy that suit for Maicih’s current business situation by considering the staging phase of Maicih and also strength, weakness and opportunity elements that Maicih has. Finally, there are six strategies offered by the researcher for Maicih. Those strategies are: promotion through TVC; put an ad or being a sponsor on radio; special promotion or event in Alfamart; present on an upcoming culinary event; young celebrity endorsement; and the last is special promo or discount for loyal consumers. Keywords: Snacks, Online Marketing, Consumer Style Inventory